Β‐Ni(OH)2 Nanosheet Arrays Grown on Biomass‐Derived Hollow Carbon Microtubes for High‐Performance Asymmetric Supercapacitors. Issue 9 (7th March 2018) - Li, Qian; Lu, Chunxiang; Xiao, Dengji; Zhang, Huifang; Chen, Chengmeng; Xie, Lijing; Liu, Yaodong; Yuan, Shuxia; Kong, Qingqiang; Zheng, Ke; Yin, Junqing
Abstract: The design and fabrication of biomass‐based energy storage devices is becoming a new trend to reduce the depletion of non‐renewable resources. Herein, β‐Ni(OH)2 nanosheet arrays grown on willow catkins‐derived hollow carbon microtubes is prepared for the first time through a facile acid treatment and subsequent hydrothermal process. In the β‐Ni(OH)2 @acid‐treated carbon microtube [β‐Ni(OH)2 @ACMT] composite, β‐Ni(OH)2 nanosheet arrays can be controllably grown on both internal and external surfaces of carbon microtubes, realizing effective utilization of the hollow tubular structure. In addition, carbon microtubes are not only employed as an effective support for the dispersion of β‐Ni(OH)2 nanosheets, but also served as a long‐range conductive micro‐current collector for electron transfer. Furthermore, the hollow tubular structure accompanied by the capillary effect provides fast channels for ion diffusion. As a consequence of this unique hierarchical structure, the electrode based on the β‐Ni(OH)2 @ACMT composite exhibits a high specific capacitance of 1568 F g −1 at 1 A g −1, remarkable capacitance retention of 51.0 % even at 20 A g −1, and excellent cycling stability of 84.3 % retention after 3000 cycles. An asymmetric supercapacitor, with β‐Ni(OH)2 @ACMT composites as the positive electrode and porous carbon microtubes as the negative electrode, achieves a high energy density of 37.8 W h kg −1 at 750 W kg −1, indicating its potential application in energy storage devices. Abstract : Inside and out : β‐Ni(OH)2 nanosheets are anchored on willow catkins‐derived hollow carbon microtubes through an acid treatment and subsequent hydrothermal process. A β‐Ni(OH)2 @acid‐treated carbon microtube (β‐Ni(OH)2 @ACMT) composite with a hierarchical structure is obtained. The hierarchical structure not only allows the external surface of the hollow tube to be suitable for charge storage, but also makes the internal surface accessible.